Study on the interaction between CaO-based sorbents and coal ash in calcium looping process - He, D.; Qin, C.; Manovic, Vasilije; Ran, J.; Feng, B. (Elsevier, 2016)
Calcium looping (CaL), implemented via cyclic carbonation and calcination of calcium-based sorbents, is a novel and promising technology in reducing emissions of CO2 into the atmosphere. The reactivity of CaO is important in calcium looping, but its CO2 sorption will be affected by the presence of ash deriving from coal combustion in the calciner. We report here, the investigation of influence of coal-derived ash on CaO-based sorbents using a thermogravimetric analyzer and a combination of other techniques. As a result of this work, our understanding of the role of several key variables (sorbent type, ash content and its particle size, the calcination conditions) and how they interact during repeated cycles of CO2 sorption and desorption, has been greatly enhanced. Furthermore, an attempt was made to explain the interaction mechanism between sorbents and coal-derived ash. It is proposed that the blockage of pores blow 3 nm due to ash deposition and subsequent grains agglomeration are the main reason for CaO-based sorbents' loss in CO2 carrying capacity.
Keywords: Calcium looping; CO2 capture; Cyclic carbonation and calcination